A couple-based gender transformative intervention to enhance women's participation in household decision-making: results from a cluster randomised control trial in Ibadan, Nigeria. Issue 8 (17th November 2021) - OlaOlorun, Funmilola M.; John, Neetu A.
ABSTRACT: Women's empowerment is recognised as an important strategy to foster gender equality. Its achievement requires an approach that targets normative and structural drivers of gender inequality. Nigerian women continue to face socio-economic challenges and are unable to exercise their agency within their homes. We evaluated a cluster-randomised control trial that aimed to increase women's household decision-making by working with couples in three critical areas: spousal relations, and financial and reproductive decision-making. The trend overall suggested gains in some domains of decision-making but the results were mixed. More research is needed for improved context-specific measurement of decision-making as well as programme adaptation.